PERAN KELUARGA DI ERA BUDAYA KONSUMEN - Elya Munfarida (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2012)
The development of consumer culture that increasingly strengthened creates verysignificant cultural implications in society. Shift in the meaning of the commodity-valueproducts in order to be a symbolic value, impact on changes in consumption practices thatoriginally was based on making the benefits of the exchange of goods became a symbol ofspace and social identity. Commodities in turn are consumed to obtain all the identities,symbols, images and signs attached to it. This in turn creates a culture where performanceimmanence (the things that are surface) occupies a higher position than anything substantial.Consequently, people are trapped in the banality of morality and spirituality, whichconsiders moral and spiritual issues as being trivial. Cultural impact is of course very crucialto be addressed so that people are not getting mired in a cycle of low moral and spiritualculture that would degrade the quality of humanity itself. In this case, the role of all levels ofsociety needs to be revitalized, and one of them is family. Family as the basic unit of societyhas many functions that are essential to be developed to address the strengthening of consumerculture. Various functions, such as religious function, social cultural function, charity function,the function of protecting, reproductive function, the function of socialization and education,including the economic and environmental development function, can make an importantcontribution to the construction of individual personality and social action. Internalizing thevalues of religion, social, cultural and other social capital will be affecting the actions andsocial practices. In relation to the negative impacts of consumer culture, education forreligious values which is related to the dimension of the divine becomes the counterculture toovercome the culture of immanence in the consumer culture.Reliance transcendental becomes an important mechanism to sensitize the public onthe need for transcendence to improve the quality of our humanity. In addition, efficientinternalization of culture or modest consumption (moderate) as confirmed in faith should bedone to limit the desire for being consumptive. This value needs to be emphasized because ithas a positive impact for the future protection of family and community in both the short andlong term.